Detecting the function of finance through history.: An essay in celebration of the work of Joost Jonker - van Bochove, Christiaan; Colvin, Christopher L.; Gelderblom, Oscar (TSEG - The Low Countries Journal of Social and Economic History, 2021)
This special review article profiles the work of Joost Jonker, who is retiring from his chair at the University of Amsterdam in 2021. We situate Joost’s work in the international literature on the financing of governments, businesses, and households, showing how his contributions to the field of financial history influence and mirror wider trends. We focus on Joost’s preferred methodology (the analytic narrative) and his preferred theoretical lens (the functional perspective). We conclude with a discussion of possible future developments in the field of financial history. Our intention is for this article to become a useful resource for new scholars entering the field of financial history, particularly on topics relating to the Low Countries.